2021
DOI: 10.1186/s13568-021-01226-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis iturin A on HepG2 cells in vitro and vivo

Abstract: Iturin A with cyclic peptide and fatty acid chain isolated from Bacillus subtilis fermentation shows a variety of biological activities. Among them, the anticancer activity attracted much attention. However, the molecular mechanism of its inhibitory effect on hepatocellular carcinoma was still unclear. Thus its effect on hepatocellular carcinoma was tested in this research. It was found that iturin A could enter HepG2 cells immediately and cause reactive oxygen species burst, disrupt cell cycle and induce apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Fengycin, a lipopeptide produced by various strains of B. subtilis, was reported to exert strong anticancer activity on colon cancer cell line HT29 and human lung cancer cell line 95D [162,163]. Similarly, Bacillus lipopeptide (iturin) was also reported to possess a broad spectrum of anticancer activity on several cell lines (e.g., HepG2, Caco-2, BT474, MDA-MB-231, MCF-7, HUVEC, BIU-87, BRL-3A, A549, and K562 cells [42,[164][165][166][167][168][169][170][171].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Fengycin, a lipopeptide produced by various strains of B. subtilis, was reported to exert strong anticancer activity on colon cancer cell line HT29 and human lung cancer cell line 95D [162,163]. Similarly, Bacillus lipopeptide (iturin) was also reported to possess a broad spectrum of anticancer activity on several cell lines (e.g., HepG2, Caco-2, BT474, MDA-MB-231, MCF-7, HUVEC, BIU-87, BRL-3A, A549, and K562 cells [42,[164][165][166][167][168][169][170][171].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Although Iturin A rescued the growth of piglets challenged by STb-R in our study, the growth-promoting effect on healthy piglets was not significant, probably due to the short duration of administration, and the effect of long-term administration of Iturin A remains to be studied. A similar study reported that Iturin A administrated for 15 d significantly inhibited tumor growth; however, there were no significant effects on body weight, food intake, and viscera index in mice [ 24 ]. Taken together, Iturin A maybe better at resisting damaging stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…The control experiment showed less consistent ALT and AST release than DMSO. The release of higher concentrations of ALT and AST are associated with subsequent damage to the hepatocellular carcinoma cells [34]. The plant extracts of A. cappadocicum increased ALT and AST in the liver tumor MPS, representing the plant extracts' efficacy against the hepatocellular carcinoma cells.…”
Section: Effect Of a Cappadocicum On Liver Function Testsmentioning
confidence: 96%